ANALISIS PENGEMBANGAN KURIKULUM DI LEMBAGA PENDIDIKAN ISLAM - Elvi Rahmi (El-Rusyd, 2021)
Curriculum development in educational institutions is inseparable from various aspects that influence it. The curriculum is an important component in education, because in the curriculum there are all educational processes from planning to implementing evaluations. The curriculum development process is the process of perfecting the existing curriculum. In accordance with the current flow of globalization, curriculum development can be seen from the various supporting and inhibiting factors that influence it. This study discusses the curriculum development process, the stages of curriculum development, and the supporting and inhibiting factors in the curriculum development process. The method used is library research which aims to examine various literatures on curriculum development. The results can find out the curriculum development process carried out to develop the curriculum in Islamic Educational Institutions.